Short-term or long-term cooperation between retailer and MCN? New launched products sales strategies in live streaming e-commerce. (July 2022) - Mao, Zhaofang; Du, Zelin; Yuan, Ruiying; Miao, Qiqi
Abstract: Nowadays, live streaming e-commerce has become popular all over the world. In this paper, we study the pricing strategy of new products when they are launched in live streaming considering the consumer uncertainty and network externalities. We characterize the impact of live streaming into two dimensions, emotional support and information support, and investigate how those two dimensions impact the choice of cooperation types and the revenue distribution between the retailer and MCN (Multi-Channel Network). Using a two-stage vertical model, we find that, with the low consumer uncertainty, the MCN induces the retailer to choose the cooperation type depending on the emotional support level, but with the high consumer uncertainty, it depends on the information support level. For new-product pricing strategy, whether to adopt the penetration pricing strategy or the skimming pricing strategy depends on the impact of live streaming, the consumer uncertainty and network externalities. Interestingly, the commission price does not increase with the consumer uncertainty. An important implication for the retailer is that, reducing consumer uncertainty may not be beneficial to the total profit.